2016
DOI: 10.1142/s1793292016500582
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Microwave Absorption Properties of CeO2 Nanoparticles Supported on Reduced Graphene Oxide

Abstract: In this work, reduced graphene oxide/CeO 2 nanocomposites (RGO/CeO 2 ) with two di®erent RGO contents were synthesized using a facile one-step hydrothermal method, and the microwave absorption properties of RGO/CeO 2 were investigated for the¯rst time. Morphology and structure analysis shows that the CeO 2 nanoparticles are uniformly dispersed on the RGO sheets with average size of 15 nm. The as-prepared RGO/CeO 2 exhibits excellent microwave absorbability. An optimal re°ection loss (RL) of À32 dB is found at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…To date, daily portable devices, such as laptops, remote controllers and smart cellphones, are vulnerable to being disturbed from GHz-level electromagnetic interference (EMI). [1][2][3][4] Not to mention that related electromagnetic (EM) pollutions severely harm the human being's health. 5,6 Nowadays, nanostructured bimetallic absorbers, like FeCo, [7][8][9] FeNi, [10][11][12] and CoNi, 13,14 are of great interest in recent choices for advanced microwave absorbers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, daily portable devices, such as laptops, remote controllers and smart cellphones, are vulnerable to being disturbed from GHz-level electromagnetic interference (EMI). [1][2][3][4] Not to mention that related electromagnetic (EM) pollutions severely harm the human being's health. 5,6 Nowadays, nanostructured bimetallic absorbers, like FeCo, [7][8][9] FeNi, [10][11][12] and CoNi, 13,14 are of great interest in recent choices for advanced microwave absorbers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it requires ideal absorbers to possess excellent trapping abilities of space charge and to endow enough converting time of attenuating the entered EMW via various forms of polarization. 1,3,5 It prompts the motivation of constructing amorphous nanostructures with abundant defects to induce additional surface/interface polarizations via doping and encapulsating. 30,31 Due to embedding secondary mediums, crystal lattices of the absorber are distorted to a®ect the unit cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, electromagnetic (EM) interference has become a great concern in the fields of electronic safety and military target stealth. Therefore, a great amount of attention has been paid to explore microwave absorbers with easy fabrication, low cost, strong absorption capability, and broad absorption bandwidth. Co, ferrites, Ni, and magnetic composites with high-efficiency microwave absorption performance have become the hot topics because of the dominant magnetic loss.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the structural, physical, and chemical properties of CeO 2 can be effectively tuned by functionalizing and compositing with dopant atoms or other compounds. For example, CeO 2 doped by Zn or composited with polyaniline and reduced graphene oxide could contribute to a better microwave absorption performance. ,, However, excellent microwave absorption properties of pure CeO 2 with hierarchical morphology have been rarely reported. Thus, to design a special hierarchical structured CeO 2 with improved performance via a facile method becomes an urgent issue.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional EMW-absorbing materials, reduced graphene oxide (rGO) has attracted much attention because of its high specific surface area, residual defects, and functional groups. , However, the high electrical conductivity of rGO displays a weak microwave-absorbing ability due to the poor impedance matching. One of the possible approachs to solve the problem is to decorate rGO with magnetic materials or a semiconductor . Therefore, a great amount of effort has been concentrated on the incorporation of rGO with magnetic constituents or a semiconductor to improve its EMW-absorbing performances. Tian et al fabricated the rGO/α-Fe 2 O 3 composite by a two-step method in a solution phase process.…”
Section: Introductionmentioning
confidence: 99%